(untitled) (Global Journal of Management and Business Research, 2015)
The main objectives of this study are twofold. The first objective is to examine the volatility spillover between the GCC stock markets and Oil prices, over the period 2005-2012, in a multivariate setting, using the VAR (1)-GARCH (1,1) model which allows for transmission in returns and volatility. The second is to investigate the dependence structure and to test the degree of the dependence between financial returns using copula functions. Five candidates, the Gaussian, the Student’s t, the Frank, the Clayton and the Gumbel copulas, are compared. Our empirical results for the first objective suggest that there exist moderate cross market volatility transmission and shocks between the markets, indicating that the past innovation in stock market have great effect on future volatility in oil market and vice versa. 0